Privacy versus the Use of Location Information for Law Enforcement and Security in Australia - Shanapinda, Stanley (Journal of Telecommunications and the Digital Economy, 2018)
This article reviews existing knowledge regarding the powers of the Australian Security Intelligence Organisation and the Australian Federal Police to access and use metadata. The review is primarily based on published research on the privacy impact of the revised metadata retention and collection framework introduced in 2015. The review reveals that, after 2015, no comprehensive study was undertaken in the following areas: how location information is generated and exchanged in the IP-mediated long-term evolution telecommunications network, and how mobile devices are tracked and create more precise location estimates, in the legal and policy context of the exceptions and privacy safeguards introduced after 2015; the discretionary powers of the agencies to use personal and sensitive information to identify inquiries and investigations to pursue, to enforce the law and perform their functions, and to carry out activities related to their functions and purposes; and the flexible oversight principles contained in the guidelines that create conflicts between law enforcement and privacy interests. The review proposes future multidisciplinary research.